2017
DOI: 10.1519/jsc.0000000000001747
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Modified German Volume Training Program on Muscular Hypertrophy and Strength

Abstract: Amirthalingam, T, Mavros, Y, Wilson, GC, Clarke, JL, Mitchell, L, and Hackett, DA. Effects of a modified German volume training program on muscular hypertrophy and strength. J Strength Cond Res 31(11): 3109-3119, 2017-German Volume Training (GVT), or the 10 sets method, has been used for decades by weightlifters to increase muscle mass. To date, no study has directly examined the training adaptations after GVT. The purpose of this study was to investigate the effect of a modified GVT intervention on muscular h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…The fact that the participants of the MAX group performed only single-set, single-repetition sets with high loads throughout the entire training intervention might have allowed them to become better at performing that specific task as seen in previous research looking at repeated 1RM tests as a mean of increasing strength [ 9 ]. Literature supports the idea that increases in strength can be achieved with both high and low volumes of training [ 14 , 15 , 16 ] but there is currently very little data on powerlifters and specifically the ‘daily max’ method. Zourdos et al [ 4 ], is the only study that looked at something similar to a ‘daily max’ protocol but as previously mentioned it investigated only the SQ and its participants trained with a very high training frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the participants of the MAX group performed only single-set, single-repetition sets with high loads throughout the entire training intervention might have allowed them to become better at performing that specific task as seen in previous research looking at repeated 1RM tests as a mean of increasing strength [ 9 ]. Literature supports the idea that increases in strength can be achieved with both high and low volumes of training [ 14 , 15 , 16 ] but there is currently very little data on powerlifters and specifically the ‘daily max’ method. Zourdos et al [ 4 ], is the only study that looked at something similar to a ‘daily max’ protocol but as previously mentioned it investigated only the SQ and its participants trained with a very high training frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Previously it was thought that following a modified GVT program for six weeks duration might be too short a timeframe for significant muscle hypertrophy adaptations to be observed [ 19 ]. Therefore, extending the duration of the modified GVT program to at least 10–12 weeks might be required to allow for these muscle adaptations [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Marshall et al [ 6 ] found no differences in squat 1RM when comparing four sets to eight sets following a six-week squat training program, although a significant increase in squat 1RM was observed for eight sets compared to one set. However, due to the relatively short duration of our previous study (i.e., six weeks) [ 19 ] as well as the other studies noted above, it is unknown whether this may have affected the results. For instance, Stark et al [ 21 ] concluded that a resistance training protocol tailored for muscle strength and hypertrophy should be at least 10–12 weeks duration involving 3–5 sessions per week.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Resistance training (RT) is an important way to intervene in health by improving muscle efficiency (Benito et al, 2020), causing muscle hypertrophy (Schoenfeld et al, 2019), and also enhancing all organic physiology (Amirthalingam, 2017;Vianna et al, 2014). Thus, studies important direct indicators to make the activity more efficient for any individual or group that comes to practice them (ACSM, 2011;Fragala et al, 2019).…”
Section: Introductionmentioning
confidence: 99%